The bamboos of Nepal and Bhutan. Part I: Bambusa, Dendrocalamus, Melocanna, Cephalostachyum, Teinostachyum, and Pseudostachyum (Gramineae: Poaceae, Bambusoideae) - Stapleton, C. M. A. (Edinburgh Journal of Botany, 2010)
Bamboos encountered during extensive fieldwork in Nepal and Bhutan are enumerated in three papers. Fifteen genera are recognized, including several genera recently described in China and one new genus. In Part I delimitation of the Himalayan bamboo subtribes and genera is discussed, and a key to the genera is given. The systematic treatment begins with six tropical and subtropical genera which all have iterauctant inflorescences and 6 stamens. Bambusa and Dendrocalamus are in the subtribe Bambusinae Agardh, having solid styles. Melocanna, Cephalostachyum, Teinostachyum, and Pseudostachyum have elongated hollow styles and are in the subtribe Melocanninae Reichenbach. Five new taxa are described: Bambusa nepalensis from central and eastern Nepal; Bambusa clavata from Bhutan; Bambusa alamii from Nepal, Bhutan, and Bangladesh; Bambusa nutans Wall, ex Munro subsp. cupulata from Nepal, Bhutan, Bangladesh, and India; and Dendrocalamus hamiltonii Nees & Arn. ex Munro var. undulatus from Nepal.